Pneumocystis Pneumonia—Is it Still a Threat Among People With Human Immunodeficiency Virus (HIV)? A Danish HIV Cohort Study - Møller, Anne K; Schnoor, Stine B; Petersen, Inge; Martin-Iguacel, Raquel; Kronborg, Gitte; Larsen, Carsten S; Dalager-Pedersen, Michael; Gerstoft, Jan; Omland, Lars H; Rasmussen, Line D (Open forum infectious diseases, 2025)
We aimed to examine pneumocystis pneumonia (PCP) risk and mortality among people with human immunodeficiency virus (HIV), and associations with (1) time after HIV diagnosis, (2) calendar time, and (3) CD4 cell count. From the Danish HIV cohort study, we identified all adult people with HIV (PWH) (1995-2021). We estimated incidence rates (IRs) and mortality rates. We used Poisson regression analysis to compute adjusted incidence ratios (IRRs) and mortality rate ratios. PCP risk was assessed according to time after HIV diagnosis, calendar time, and low CD4 cell count. Among 4882 PWH (53 647 person-years), we observed 336 PCP events (for the time period 2016-2021 compared to 1995-1999, PCP risk decreased by >90% after the first year of HIV diagnosis; aIRR, 0.08 [95% confidence interval CI, .02-.29], and by >40% in the first year, if baseline CD4 count was <200 cells/µL [aIRR, 0.57 [95% CI, .36-.90]). However, no statistically significant change in PCP risk was observed after 1995-1999 for the latter group. PCP risk remained high if the CD4 count was 100 to <200 cells/µL (IR, 16.08 [95% CI, 5.19-49.89]) during the first year of combination antiretroviral therapy (cART), despite a suppressed viral load. Major reductions were found after 1 year of cART (CD4 count 100 to <200 cells/µL). Although nonsignificant, the 3- and 12-month mortality rate decreased by 80% from 1995-1999 to 2016-2021. PCP remains a significant problem among late presenters with HIV, emphasizing the importance of early HIV diagnosis. Continuing PCP prophylaxis until the CD4 count is >100 cells/µL, with at least 1 year of cART and viral suppression for >3 months should be considered; however; further studies are needed to confirm these results.